Penerapan Strategi True Or False Mata Pelajaran Fiqih Untuk Meningkatkan Hasil Belajar Siswa Kelas VII MTs Al-Ikhwan Serapuh ABC - Arlina, Arlina; Maharani, Alya Wira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was motivated by the lack of creativity of fiqh teachers in class VII MTs Al-Ikhwan Sefragile ABC so far in exploring learning designs that can be used for monotonous fiqh subjects so that students tend to feel bored, for this reason there needs to be a paradigm shift in reviewing teaching and learning strategies and regulating teacher and student interactions, applying true or false strategies in the fiqh learning process in class VII MTs Al-Ikhwan Sefragile ABC is One way to improve existing learning methods. This study is intended to answer the problem: Can the True or False strategy improve student learning outcomes on halal and haram food materials in class VII MITs Al-Ikhwan Sefragile ABC? These quentions were discussed in two cycles of classroom behavioral reseacrh. The sequence of stages includes plan, act, observe, and consider. The results show that: Can the True or False strategy improve student learning outcomes on halal and haram food materials in class VII MTs Al-Ikhwan Sefragile ABC? These problems are discussed through classroom action research carried out through 2 cycles with each cycle of stages being planning, action, observation, and reflection. The results are as follows. In Class VII MTs, correct or incorrect strategies can improve students' learning outcomes on halal and haram ingredients. Al Ifwan Sephrazir ABC. Cycle students only 53.1% Cycle I 65.3%, Cycle II 85.6%.